Quality retention during the chilled distribution of farmed turbot (Psetta maxima): effect of a primary slurry ice treatment - Piñeiro, Carmen; Bautista, Raquel; Rodríguez, Óscar; Losada, Vanesa; Barros-Velázquez, J.; Aubourg, Santiago P. (International Journal of Food Science and Technology, 2005)
8 páginas, 4 tablas The quality and shelf-life of chilled farmed turbot (Psetta maxima) was evaluated by sensory, microbiological and biochemical procedures after being subjected to a two-step refrigeration storage in slurry ice and flake ice, respectively. Turbot specimens were stored for 10 or 17 days in slurry ice, and then were transferred to flake ice for 1–3 days to simulate the sale conditions in the market. The results were compared with control batches stored only in flake ice and processed in parallel. Storage of turbot in the two-step strategy resulted in a better maintenance of sensory quality, especially with regard to its mucus production and gill odour development, better control of microbial activity, especially of aerobes, and the slowing down of some biochemical degradation mechanisms such as the nucleotide degradation pathway and trimethylamine production. As a consequence, the shelf-life was extended significantly. From these results it can be concluded that the refrigerated transport of farmed turbot in slurry ice enhances its shelf-life, before its transfer into flake ice in the retail market This project was supported by a grant from the Secretarı´ a Xeral de I + D from the Xunta de Galicia (Spain) (Project PGIDT 01 MAR 40202 PR). Peer reviewed